Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) untuk Meningkatkan Keterampilan Sosial Siswa Madrasah Ibtidaiyah - Arum Putri Lestari; Diana Lestari; Kamila Tunnisa; Yova Emelia Putri (JPT : Jurnal Pendidikan Tematik, 2025)
This study aims to examine the effectiveness of the Think Pair Share (TPS) cooperative learning model in improving the social skills of elementary school (MI) students. The research method used is classroom action research (CAR) with two cycles, each of which includes planning, implementation, observation, and reflection. The subjects of the study were 28 fifth grade students of MI, Bengkulu City. The results showed that the TPS model can significantly improve students' social skills, especially in the aspects of communication, cooperation, active listening, and tolerance of differences. The average social skills score increased from 65 to 85. These findings confirm that the TPS model is able to create collaborative learning that strengthens social interaction in the madrasah environment. This study provides recommendations for PGMI teachers to integrate the TPS model into daily learning strategies.